Children's Responses to Negative News: The Effects of Constructive Reporting in Newspaper Stories for Children. (24th August 2017) - Kleemans, Mariska; de Leeuw, Rebecca N. H.; Gerritsen, Janel; Buijzen, Moniek
Abstract : For a well‐functioning democracy, it is crucial that children consume news. However, news can elicit overly negative emotions and discourage engagement in children. The question, therefore, is how news can be adapted to children's sensitivities and needs but can still inform them. This study investigated whether constructive reporting (solution‐based narratives including positive emotions) in news about negative events improved emotional responses and encouraged engagement (intention and inspiration to engage). In an experiment, 8–13‐year‐olds ( N = 332) read a story containing either constructive elements or not. Constructive news elicited lower levels of negative emotional responses and provided more inspiration for engagement than nonconstructive news. These promising findings open doors for follow‐up investigations regarding constructive news reporting, also among adult audiences.